Antibacterial effectiveness of garlic (Allium sativum Linn.) extract nanoparticles against E.faecalis: Efektivitas antibakteri nanopartikel ekstrak bawang putih (Allium sativum Linn.) terhadap E.faecalis - Juni Jekti Nugroho; Tharisya Amiharna Kayla; Afniati Rachmuddin (Makassar Dental Journal, 2024)
To determine the antibacterial effectiveness of 2.5% sodium hypochlorite (NaOCl) irrigation solution and garlic extract nano-particles (Allium sativum Linn.) against Enterococcus faecalis. This type of research is an in vitro laboratory experiment with a post-test only with control group design using the dilution method. The research sample consisted of garlic nanoparticles, 2.5% NaOCl, and distilled water with each repetition carried out 3 times. The antibacterial ability is based on the inhibition zone formed around the stainless-steel cylinder on the MHA medium. Data processing and analysis techniques were carried out using the Shapiro Wilk test and one-way Anova. The average diameter of each inhibition zone for the antibacterial of garlic extract nano-particles with concentrations of 20%, 30% and 40% was 30.69±1.03 mm, 34.73±1.09 mm and 39.66±2.14 mm, meanwhile 2.5% NaOCl showed an average inhibition zone diameter of 35.49±0.55 mm. It is concluded that garlic extract nanoparticles concen-centrations of 20%, 30% and 40% have a very strong antibacterial effect against E.faecalis.